Interpretation of the concepts of «individuality» and «individualization» by Chinese scientists - Yue, Wu; Yakimova, Maryna (Professional Art Education, 2024)
The article analyzes the approaches to defining the categories of “individuality” and “individualization” by Chinese scientists in the context of a comparative study of the problem of individualization of vocal training in higher educational institutions of the PRC. Object. The relevance of the study is determined by the need to exchange experience in implementing the humanistic paradigm of modern education. It is stated that the study of the conceptualization of concepts of the terminological field of this problem by Chinese researchers will allow us to better understand the originality of their approaches to building appropriate educational practice, will make it possible to effectively use pedagogically valuable ideas in the modern conditions of development of Ukrainian higher musical and pedagogical education. Methods & methodology. Based on the analysis of reference and scientific and pedagogical literature, the approaches of Chinese authors to defining the concepts of “individuality” and “individualization” are revealed. Attention is focused on their interpretation of the categories “person”, “individual”, “personality”, “socialization”. Separately, the approaches to defining the concept of «aesthetic individuality» are outlined. It is found that it is interpreted as a characteristic of the uniqueness of the individual as the primary source of exclusivity, diversity and richness of creative expression; the ability of a person to create unique aesthetic judgments and manifest creative potential through the peculiarities of his own perception. Scientific novelty. The presence of different points of view on the relationship between the terms «personality» and «individuality», «individualization» and «socialization» is stated. Results. Views on the interrelated features of individuality are generalized: originality, uniqueness, uniqueness, ability to develop, stability and changeability, complexity, integrity, the presence of one’s own «I», identity with oneself, independence, autonomy, freedom, active and creative nature of the individual, existence. Conclusions. The emphasis placed by Chinese scholars when interpreting the concept of «individualization» on the transformation, strengthening, and complication of a person’s individual characteristics, the realization of his or her uniqueness, the formation of self-awareness, and the growth of self-conformity is emphasized. Their views on the mechanism of individualization are clarified.